The 3-year follow-up of a fully biodegradable implantable device closure for perimembranous ventricular septal defects in children using echocardiography - Cong, Juan; Cui, Cunying; Huang, Danqing; Wang, Ying; Liu, Sifan; Song, Shubo; Fan, Taibing (Frontiers in Cardiovascular Medicine, 2024)
Objects The aim of this study was to investigate the morphologic changes of a novel fully biodegradable implantable device after closing a perimembranous ventricular septal defect (Pm-VSD) and to evaluate the effect of the occluder on the myocardial function in patients during a 3-year follow-up period. Methods One-year, 2-year, and 3-year follow-ups were carried out after implantation with a total of 30 Pm-VSD patients who had successful closure by the fully biodegradable occluder. In total, 30 healthy children were enrolled as controls. At discharge and at every follow-up visit, the lengths of the left and right discs of the novel device were measured in the apical three- and four-chamber as well as short-axis views. At the end of the follow-up, using three-dimensional speckle-tracking conditions, the values of myocardial deformation, including global longitudinal strain, global circumferential strain, and global area strain, were acquired. Results The fully bioabsorbable double-disc occluder gradually decreased over time and was eventually invisible under echocardiographic scanning during the follow-up (p < 0.05). At the end of the third year, there were no significant differences in the myocardial deformation parameters between the cases implanted with the novel devices and the controls; no significant differences were found between the basal segments of the ventricle septa and that of the left ventricle (LV) free wall among the patients who completed the Pm-VSD closure using the fully biodegradable occluder (p > 0.05). Conclusion The novel fully biodegradable occluder is a safe, effective, and perfect alternative for the treatment of VSD. Echocardiography plays a crucial role in the follow-up of this new type of occluder implantation.